3 log_10(x^2)-log_10^2(-x) = 9
Not really sure how to deal with the log(-x). What can I do with this equation?
Also, when dealing with logarithms, is checking for extraneous solutions essential? What constitutes that a certain logarithmic equation will not yield extraneous solution? Or is it pure arbitrary?
substitute
u = -x
Now you have:
3 log_10(u^2) - log_10^2(u) = 9
and continue....
What happens to the first term when you substitute u = -x? Does the 3 log_10(x^2) ---> 3 log_10((-u)^2) ---> 3 log_10(u^2) ?